ANALISA TEKNIS PENGGANTIAN MESIN INDUK KAPAL PATROLI KP. PARIKESIT 513 - Manik, Parlindungan; Kiryanto, Kiryanto (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2009)
Technical analysis main engine replacement of patrol boat was selected as a research object because main engine replacement with lower power, that is from 2 x 1448 BHP become 2 x 1100 BHP so that happened degradation of ship’s speed on duty from 15 knot become 16 knot. The planning of optimal propeller design and gear box ratio even from reached speed, propulsion efficiency, dan fuel oil consumption become the solution to make the optimal consequence to overall propulsion system of the ship. Propellers which analysed were Wageningen B3- series and B4- series with variation input of diameter which in range 0,6-0,7 T, variation input of expanded area ratio, and variation input of pitch diameter ratio. In this propeller performance analysis aided by P.O.P. (Propeller Optimization Program) software.The overall propeller performance analysis show there were 2 type of propeller B3- series and 2 type of B4 series which have the highest propulsion efficiency. From the propeller types were made Propeller-Engine Matching graph. The Matching Point was a most optimal propeller performance, and then that point was plotted to the FOC graph of main engine to know amount of fuel oil which consumed.Type of propeller which were having the highest propulsion efficiency at Matching Point were type B3-35 P/D 0,8 Diameter 1600 mm (67,1%), type B3-35 P/D 1,0 Diameter 1600 mm (66,3%), type B4-55 P/D 1,0 Diameter 1600 mm (64,9%), type B4-70 P/D 1,0 Diameter 1600 mm (64,8%)